Blood-Sparing Technique during Surgical Treatment of Aortic Valve Disease under Cardiopulmonary Bypass - Gumeniuk, B. M.; Popov, V. V.; Gurtovenko, A. N.; Klimenko, S. N. (Ukrainian Journal of Cardiovascular Surgery, 2019)
The use of donated blood components in patients with acquired heart defects in the operative period is often associated with a variety of possible complications requiring the search for alternative measures to reduce their use. In the pe-riod from 01/01/2011 to 01/01/2019 at the Department of Surgery of Acquired Heart Defects of National Amosov Institute of Cardiovascular Surgery, isolated aortic valve replacement was performed in 680 patients divided into 2 groups. The main group included 452 patients in whom no donated blood components were used at the operative stage, and the comparison group included 228 patients who obtained blood products during the operative period. The technique of anesthesiological and perfusiological measures at the “bloodless” aortic valve replacement under cardiopulmonary bypass is described. In the main group, autologous blood collection in pre-perfusion period was not marked by sharp hemodynamic changes. Acute normovolemic hemodilution was performed with a 6% hydroxyethyl starch solution in a 1:1 ratio. The levels of Hb, Hct and protein during the surgical intervention were at the stage of compensation. At Hct ≥39, autologous blood was collected (variant A) before heparin administration. Under the central venous pressure control, water balance was evaluated during stimulation of diuresis. Variant A was perdominantly used. For variant A, Hb decrease from 13.6 g/L to 11.9 g/L, and blood protein decrease from 67.4 ± 4.1 g/L to 61.5 ± 5.2 g/L were observed. The retrograde antological priming (RAP) variant B (displacement from the perfusate tank) was used in 11.4% of the total. In the comparison group, 511.8 ± 117.7 ml of packed RBC and 564.9 ± 63.3 ml of fresh frozen plasma per patient were transfused in the operating period. The length of stay in the ICU was 64.7 ± 16.8 hours in the main group, 87.2 ± 24.6 hours in the comparison group. The time spent in the surgical hospital was 9.2 ± 1.1 days in the main group and 11.8 ± 3.3 days in the comparison group. Implementation of the procedure described enabled to obtain good clinical effect without transfusion complications at the hospital stage.